Optimalisasi Pengelolaan Lingkungan Desa Air Kering 1 Melalui Pemberdayaan Masyarakat - Terry, Leoni; Sentosa, Anugerah Anggun; Prantio, Alan; Islaini, Yulia; Nurzam, Nurzam; Susena, Karona Cahya; Handayani, Tita (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The thematic community service (Kuliah Kerja Nyata Tematik) Group 29 from Universitas Dehasen Bengkulu (Period III, 2025) was conducted in Air Kering 1 Village (Padang Guci Hilir District, Kaur Regency, Bengkulu). The project aimed to optimize environmental management and community empowerment. The main issues identified were the lack of an integrated waste management system, low public awareness of cleanliness, and limited educational/religious activities for youth. The implementation involved cleaning riverbanks, constructing a communal waste bin, organizing religious literacy activities (communal prayers and Quranic study), and planting avocado seedlings; all activities were carried out participatively with villagers. Results showed a cleaner river, an operational waste bin, 40 avocado trees planted, and increased religious and social activities. Consequently, villagers’ environmental awareness improved, and social ties were strengthened. The program effectively addressed the identified problems, particularly waste management and community cohesion. In conclusion, this community service contributed positively to environmental cleanliness and social harmony. Recommendations include sustaining the waste management program and providing further training in waste handling and organic farming.